Bibliometric Analysis of Agropreneurship - Judijanto, Loso; Soelistianto, Farida Arinie; Nugroho, Budi (Westscience Press, 2025)
Agropreneurship, the integration of agriculture and entrepreneurship, has gained significant attention as a means of fostering economic growth, rural development, and sustainable agricultural practices. This study employs a bibliometric analysis to assess the research landscape of agropreneurship, using Scopus as the primary data source and VOSviewer for analytical visualization. The findings reveal key thematic clusters, including innovation, sustainability, policy interventions, and entrepreneurial behaviors, which highlight the multidisciplinary nature of agropreneurship research. The study also identifies emerging trends such as digital agropreneurship, climate-smart agriculture, and financial support mechanisms for smallholder farmers. Despite the growing interest, research fragmentation and the need for greater interdisciplinary collaboration remain challenges. The study concludes that fostering technological integration, strengthening market access, and enhancing policy frameworks are critical to advancing agropreneurship. Future research should focus on addressing these gaps to support sustainable agricultural entrepreneurship and global food security.